Justification approach to reducing the intensity of the aerial photograph informative segments that carry information about the landscape - Красноруцький, А.О. (Science-based technologies, 2017)
In the article the problem of providing justification for reducing information redundancy aerial photos obtained from the board of unmanned aircraft systems, preserving semantic information. The analysis of existing technologies reduces information redundancy aerial photograph. It is proved that one of the ways to reduce the intensity information of the source image segments with semantic preserving its integrity is the use of approaches based on combinatorial localization structurally redundancy. It suggested the direction of improving the methods of elimination of redundancy in the informative segments that carry information about the landscape through the provision of relevant and meaningful semantic areas of the image. Identified scientific and applied research direction: reducing the time required for image processing, taking into account the structural and combinatorial features an aerial photo of segments carrying information about the landscape and the conservation of the semantic information content of such segments. Justified conditions to develop a method of forming an effective syntactic representation segments, which carry information about the landscape.